HUBUNGAN RIWAYAT PEMBERIAN ASI EKSLUSIF, KELENGKAPAN IMUNISASI DASAR, DAN DURASI SAKIT TERHADAP STATUS GIZI BALITA DARI IBU PEKERJA PABRIK di KECAMATAN GROGOL KABUPATEN SUKOHARJO: The Correlation Between History of Exclusive Breastfeeding, Completeness of Immunization, Duration of Illness, with The Nutritional Status of Toddlers from Factory Workers Mother in Grogol, Sukoharjo - Diva Amalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2020)
History of exclusive breastfeeding, completeness of immunization, and duration of illness occurrence in toddlers are some of the factors that influence the nutritional status of toddlers. Especially toddlers with mothers who work as factory workers. That is because, mothers who work as laborers or factory workers have limited time at home so they pay less attention to child care. According to preliminary survey results as much as 0.47% of toddlers experience malnutrition status and 3.44% of toddlers experience underweight status. The purpose of this research is to find the correlation between history of exclusive breastfeeding, completeness of immunization, and duration of illness with the nutritional status of toddlers from factory workers mother in Grogol, Sukoharjo. This type of research is an observational study with cross sectional data collection methods. Bivariate analysis used in this study is the correlation test, and the Fisher Exact test. There was no correlation between the history of exclusive breastfeeding (p = 0.338), the completeness of basic immunization (p = 1.00), and the duration of illness with the nutritional status of toddlers from factory workers mother in Grogol, Sukoharjo (p = 0.235).